(untitled) (Homoeopathy for All, 2024)
plays a critical role in maintaining physical and mental health. It is essential for various bodily functions such as cognitive processing, emotional regulation, and systemic homeostasis.1 The quality of sleep significantly impacts overall well-being, with poor sleep linked to various health issues, including cardiovascular diseases, obesity, diabetes, and mental health disorders like depression and anxiety.2, 3 In recent years, the prevalence of sleep disorders has been rising, with common conditions including insomnia, characterized by difficulty in falling or staying asleep; sleep apnea, marked by interrupted breathing during sleep; restless leg syndrome, featuring an uncontrollable urge to move the legs; and circadian rhythm disorders, affecting the sleep-wake cycle.4 These conditions not only diminish quality of life but also pose a burden on healthcare systems.